The effect of soybean tempeh milk and soybean tempeh youghurt on fatigue after maximal excercise - Misi Suci Wusono; Hardhono Susanto; Etika Ratna Noer; Muflihatul Muniroh; Diana Nur Afifah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Studies report skeletal muscle fatigue during repeated intense muscle contractions resulting from depletion of energy substrates, and accumulation of metabolic. Creatine kinase (CK) and lactic acid are enzymes that are directly related to energy metabolism. This study aims to analyze the differences of soy tempeh milk and soy tempeh yogurt on fatigue indicators, namely CK levels and lactic acid in subjects induced by maximum exercise. The subjects of this study used experimental animals, namely white rats with a total sample of 28 rats. The dose of soy tempeh milk and soy tempeh yogurt given was 4,2 ml/BW of rats while the soy tempeh yogurt was given was 4,4 ml/BW, each containing 3 grams of tempeh. Blood samples were tested using the Elisa method and the results were analyzed using SPSS version 20. The results of this study showed significant changes in serum CK and lactic acid after being given the intervention of soy tempeh milk and tempeh yogurt (p<0,05). Soy tempeh milk and soybean tempeh yogurt significantly suppressed the increase in CK and lactic acid in rats induced by maximum exercise. Both provide protein containing BCAAs which are a source of energy during exercise. Further clinical trials are needed to determine the effectiveness, safety, and side effects of soy tempeh milk or soy tempeh yogurt when given to humans.